(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The ideas developed in this paper bring out an informative relevance of Auteur Theory, its origin and development in the cinematic progression of acceptance and rejection, deconstructing the age-old notion of established parameters. Here, it is stated how the role of director is significant, likened to a writer or painter, who not only understands the prevalent consciousness of the taste but at the same time recreate a logical, philosophical and cinematic discourse with the camera which enters into the cinematic representation of characters, situations and symbolism.